2022
DOI: 10.1161/circulationaha.121.057639
|View full text |Cite|
|
Sign up to set email alerts
|

Aortic Valve Replacement Versus Conservative Treatment in Asymptomatic Severe Aortic Stenosis: The AVATAR Trial

Abstract: Background: Surgical aortic valve replacement (SAVR) represents a class I indication in symptomatic patients with severe aortic stenosis (AS). However, indications for early SAVR in asymptomatic patients with severe AS and normal left ventricular function remain debated. Methods: The Aortic Valve replAcemenT versus conservative treatment in Asymptomatic seveRe aortic stenosis (AVATAR) trial is an investigator-initiated international prospective randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(84 citation statements)
references
References 29 publications
3
79
0
2
Order By: Relevance
“…In recent years, published large randomized trials and meta-analyses demonstrated non-inferiority and even superiority concerning major adverse cardiac events (MACE) favoring TAVR over SAVR across the spectrum of AS-patients, irrespective of baseline surgical risk ( 20 – 24 ). In addition, recently presented the Aortic Valve ReplAcemenT vs. Conservative Treatment in Asymptomatic SeveRe Aortic Stenosis (AVATAR) randomized trial demonstrated benefit of early SAVR in asymptomatic patients with severe AS and normal LV ejection fraction ( 25 ). Expert consensus opinion (class IIa, level of evidence C) highlights that percutaneous coronary intervention (PCI) should be considered in AS-patients with a primary indication to undergo TAVR who have stenosis of at least 70% DS in the proximal segments of epicardial coronary arteries that subtend a large area of myocardium at risk ( 7 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, published large randomized trials and meta-analyses demonstrated non-inferiority and even superiority concerning major adverse cardiac events (MACE) favoring TAVR over SAVR across the spectrum of AS-patients, irrespective of baseline surgical risk ( 20 – 24 ). In addition, recently presented the Aortic Valve ReplAcemenT vs. Conservative Treatment in Asymptomatic SeveRe Aortic Stenosis (AVATAR) randomized trial demonstrated benefit of early SAVR in asymptomatic patients with severe AS and normal LV ejection fraction ( 25 ). Expert consensus opinion (class IIa, level of evidence C) highlights that percutaneous coronary intervention (PCI) should be considered in AS-patients with a primary indication to undergo TAVR who have stenosis of at least 70% DS in the proximal segments of epicardial coronary arteries that subtend a large area of myocardium at risk ( 7 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that surgery should be considered in asymptomatic patients and in patients with aortic stenosis at earlier stages in order to reduce the risk of surgical intervention. The use of echocardiography capabilities is an effective strategy in this cohort of patients [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The early recognition and management of this pathology are very important because untreated asymptomatic and symptomatic severe diseases result in poor outcomes if managed with conservative treatment. In these patients, therefore, aortic valve replacement (AVR) represents the treatment of choice (1)(2)(3)(4). New prostheses have been developed to minimize the surgical risk in patients with multiple comorbidities and to reduce operating times.…”
Section: Introductionmentioning
confidence: 99%